PENINGKATAN KETERAMPILAN MENULIS KARANGAN PERSUASI DALAM PEMBELAJARAN TEMATIK MENGGUNAKAN MEDIA POP UP BOOK PADA SISWA SEKOLAH DASAR - Putri, Annisa Dwi; Sumianto, Sumianto; Jon, Jon (Jurnal Muassis Pendidikan Dasar, 2023)
This study aims to describe the skills of writing persuasive essays in thematic learning using pop up book for elementary school students. The method used is a classroom action research method, the research was conducted at Elementary School 005 Langgini, Bangkinang District, Kampar Regency, Riau Province. Subjects used in this study were class fifth with a total of  25 students consisting of 10 boys and 15 girls. Results of this study can be seen from the completeness of the cycle, it is found that in the pre-action activities, the class average score is 57.8 with classical completeness of 52%, increasing in cycle 1 meeting 1 to 60.2 with classical completeness of 56%, increasing in cycle 1 meeting 2 to 66.4 with classical completeness of 64%. The average value of the class in cycle 2 meeting 1 is 74.4 with classical completeness of 76%, and increased in cycle 2 meeting 2 which is 76.6 with classical completeness of 84%. Conclusion of this research is that through for media Pop Up Book in thematic learning for fifth grade students at Elementary School 005 Langgini can improve student learning outcomes in improving persuasive essay writing skills in thematic learning using Pop Up Book media elementary school students.